Regulation of Gonadotropin-Releasing Hormone-(1–5) Signaling Genes by Estradiol Is Age Dependent - Bauman, Bradly M.; Yin, Weiling; Gore, Andrea C.; Wu, T. John (Frontiers in Endocrinology, 2017)
Gonadotropin-releasing hormone (GnRH) is a key regulatory molecule of the hypothalamic-pituitary-gonadal (HPG) axis that ultimately leads to the downstream release of estradiol (E2) and progesterone (P). These gonadal steroids feed back to the hypothalamus and pituitary to regulate reproductive function and behavior. While GnRH is thought to be the master regulator of reproduction, its metabolic product GnRH-(1-5) is also biologically active. Thimet oligopeptidase 1 (THOP1, also known as EP24.15) cleaves GnRH to form GnRH-(1-5). GnRH-(1-5) is involved in regulation of the HPG axis, exerting its actions through a pair of orphan G protein-coupled receptors, GPR101 and GPR173. The physiological importance of GnRH-(1-5) signaling has been studied in several contexts, but its potential role during reproductive senescence is poorly understood. We used an ovariectomized (OVX) rat model of reproductive senescence to assess whether and how GnRH-(1-5) signaling genes in hypothalamic subnuclei change in response to aging and/or different estradiol replacement regimens designed to model clinical hormone replacement in women. We found that Gpr101 and Gpr173 mRNA expression was increased with age in the arcuate nucleus (ARC), while expression of Gpr173 and EP24.15 increased with age in the medial preoptic area (mPOA). Treatment with E2 in younger OVX animals increased expression of Gpr101, Gpr173, and EP24.15. However, older animals treated with E2 showed decreased expression of these GnRH-(1-5) signaling genes, displaying an age-related decline in responsiveness to E2. To our knowledge, this is the first study to systematically assess the effects of age and different clinically-relevant regimens of E2 replacement on GnRH-(1-5) signaling genes.